PERANCANGAN DAN PEMBUATAN HARDWARE DIGITAL SIGNAGE MENGGUNAKAN LED P4 RGB BERBASIS RASPBERRY PI - Muharram Apri Linorfah; Rizadi Sasmita Darwis; Hamid Azwar (Politeknik Caltex Riau, 2021)
In the digital era, information boards have migrated from conventional forms to digital forms, hence the term digital signage. Digital signage is a digital device that has been programmed to display information through a monitor board, LCD TV, PLASMA TV, projectors, and digital billboards. Currently, it is very common for us to pay attention to an information board in offices, in lecture buildings, at airports, and train stations in the form of a flat screen monitor controlled by a computer. Among them, the media can only be placed in one place and it is relatively difficult to move. Therefore, the use of computers will be replaced by using raspberry pi as the operating medium. This research includes raspberry pi, RGB LED as a screen to display information and the web to change data or information displayed on the RGB LED screen. Based on the research conducted, it was found that data in the form of images or videos can be displayed on the RGB LED screen using the web.